Elucidating Copper Dissolution Phenomenon in Li-Ion Cells under Overdischarge Extremes. Issue 9 (5th June 2018) - Fear, Conner; Juarez-Robles, Daniel; Jeevarajan, Judith A.; Mukherjee, Partha P.
Abstract : The mechanisms driving the thermo-electrochemical response of commercial lithium-ion cells under extreme overdischarge conditions (< 0.0 V) are investigated in the context of copper dissolution from the anodic current collector. A constant current discharge with no lower cutoff voltage was used to emulate the effects of forced overdischarge, as commonly experienced by serially connected cells in an unbalanced module. Cells were overdischarged to 200% DOD (depth of discharge) at C/10 and 1C rates to develop an understanding of the overdischarge extremes. Copper dissolution began when a cell reached its minimum voltage level (between −1.3 V and −1.5 V), where the anode potential reached a maximum value of ∼4.8 V vs. Li/Li + . Deposition of copper on the cathode, anode, and separator surfaces was observed in all overdischarged cells, verified with EDS/SEM results, which further suggests the formation of internal shorts, although the cell failures proved to be relatively benign. The maximum cell surface temperature during overdischarge was found to be highly rate-dependent, with the 1C-rate cell experiencing temperatures as high as 79°C. Concentration polarization and solid electrolyte interphase (SEI) layer breakdown prior to the initiation of copper dissolution are proposed to be the main sources of heat generation during overdischarge.